Cold comfort: Covid-19, lockdown and the coping strategies of fuel poor households. (November 2021) - Ambrose, Aimee; Baker, William; Sherriff, Graeme; Chambers, Joseph
Abstract: The number of households experiencing fuel poverty is thought to have risen by at least 600, 000 in the UK because of the ongoing Covid-19 pandemic. The concentration of fuel poor households in poor quality, energy inefficient accommodation that they have little power to improve means they are particularly negatively affected by the retreat into the home brought about by successive lockdowns and restrictions. For many such households, the home is not the place of sanctuary that it needs to be at a time like this. However, our empirical research into the lived experiences of fuel poverty reveals additional consequences for fuel poor households, chiefly associated with restricted access to third spaces and other disruptions to their usual coping strategies. Based on our evidence, we highlight three key considerations for policy on fuel poverty in the era of Covid-19: the need to rapidly upgrade the energy performance of the existing housing stock; the need to address the additional financial hardship faced by fuel poor households; and the need to prioritise access to third spaces and high-quality public spaces while restrictions last. This paper develops the concept of energy poverty by considering the role of spaces outside the home as part of the overall experience of energy poverty and the range of ways in which policy makers can mitigate its impacts.